'Picture imperfect': the motives and uses of patient photography in the asylum. Issue 2 (June 2023) - Dahlquist, Caroline; Kinderman, Peter
In the nineteenth century, photography became common in psychiatric asylums. Although patient photographs were produced in large numbers, their original purpose and use are unclear. Journals, newspaper archives and Medical Superintendents' notes from the period 1845–1920 were analysed to understand the reasons behind the practice. This revealed: (1) empathic motivation: using photography to understand the mental condition and aid treatment; (2) therapeutic focus on biological processes: using photography to detect biological pathologies or phenotypes; and (3) eugenics: using photography to recognise hereditary insanity, aimed at preventing transmission to future generations. This reveals a conceptual move from empathic intentions and psychosocial understandings to largely biological and genetic explanations, providing context for contemporary psychiatry and the study of heredity.